Studies on the phenotypic variation in growth stress intensity and its association with tree and wood properties of South African grown Eucalyptus grandis (Hill ex Maiden) - Malan, F. S. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 1984.